2011
DOI: 10.1590/s1984-70332011000400007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro viability and preservation of pollen grain of kiwi (Actinidia chinensis var. deliciosa (A. Chev.) A. Chev)

Abstract: -Kiwi is a dioecious plant species, requiring cross pollination for fruit production. The objective of this study was to evaluate the in vitro viability and shelf life of pollen grains of two kiwi varieties. Flowers of the cultivars Matua and Tomuri were collected and the pollen germinated in vitro, in culture medium containing agar (1 %), sucrose (0, 5, 10, 20 and 40 %) and boric acid (0 and 50 mg L -1 H 3 BO 3 ). Pollen grains were stored in a BOD incubator (25.0 °C), refrigerator (4.0 °C), freezer (-18.0 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…Another research on Carica papaya L. "Washington" pollen which was freeze-dried and stored at −20˚C for 14 months showed that artificial pollination using stored pollen produced fruit set [21]. There are also similar studies on different species such as [22] and [23]. Although the importance of pollen storage about fertilization and germination abilities has been mentioned and the related studies were conducted, it seems that the researches about effects of stored pollens on fruit quality characters are not common or has not yet in-terested.…”
Section: Introductionmentioning
confidence: 99%
“…Another research on Carica papaya L. "Washington" pollen which was freeze-dried and stored at −20˚C for 14 months showed that artificial pollination using stored pollen produced fruit set [21]. There are also similar studies on different species such as [22] and [23]. Although the importance of pollen storage about fertilization and germination abilities has been mentioned and the related studies were conducted, it seems that the researches about effects of stored pollens on fruit quality characters are not common or has not yet in-terested.…”
Section: Introductionmentioning
confidence: 99%
“…The protracted storage time increases the portion of pollen grains able to germinate for nine wild rose species that showed viability higher or similar to that before storage at −25 °C for six months [ 12 ]. The kiwi pollen grains of the cultivar “Tomuri”, stored in the refrigerator or in the freezer, can be used for pollination in the same growth cycle [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of boron, pollen tubes show abnormalities like coiling and bursting. Boron impacts pollen germination and pollen tube growth in three ways: it promotes absorption of sugars; it increases oxygen uptake; and also it is involved in the synthesis of pectic material for the wall of the actively growing pollen tube [6,25]. The key factor in achieving successful germination and to manipulate pollen tube growth is the osmolarity of pollen germination solution [26].…”
Section: Pollen Viability Test After Storagementioning
confidence: 99%